Faktor-Faktor Kemenangan Ridwan Kamil dan Uu Ruzhanul Ulum Dalam Pilkada Jawa Barat Tahun 2018 - Gina Yuliana Dewi; Dewi Erowati (UIN Mataram, 2021)
In the 2018 West Java regional elections competition, four pairs of candidates appeared as candidates for Governor and Deputy Governor. The new candidates for the 2018 West Java Governor elections candidacy, namely the pair Ridwan Kamil and Uu Ruzhanul Ulum, came out as winners in the West Java Governor elections constellation. This pair was able to defeat the incumbent in the people's democratic party. The problem that underlies this research is how new candidates can beat incumbents and candidates promoted by the winning party in the West Java legislative election. Based on these problems, it becomes interesting to study because new candidates can get a winning seat. Of course, victory is achieved through careful preparation and the strategies used by their winning team. Also, there were some factors that influenced Ridwan Kamil and Uu Ruzhanul Ulum's victories. This paper aims to determine what factors influence the victory of the pair who also managed to beat the incumbent and the winning party in the legislative elections in West Java. This research uses qualitative research methods, with data collection through interviews and documentation techniques. Through the research method used, we can see what factors influence the victory of this candidate pair. Sources in this study were representatives of the West Java NasDem Regional Leadership Council team, former Ridwan Kamil's vision and mission drafting team, volunteers, and the voting community. The results showed that the victory was not obtained from the number of votes of parties supporting the legislative elections and incumbent factors, but some factors influenced the victory. First, the popularity factor of Ridwan Kamil, who is a young, creative, visionary and innovative figure. This factor was chosen by millennial groups and rational voters in West Java. Second, the political machine factor because in order to get a ticket to go to the regional elections, the candidates who run are generally supported by the strength of the coalition of supporting parties that are joined behind them and the strategies used by the winning party team. Third, volunteering also makes a major contribution to increasing the voice. Fourth, community participation is the determinant of victory because in the 2018 West Java regional elections, community participation increased significantly compared to the previous regional elections. Fifth, modalities which include political capital, social capital, and cultural capital. The political capital owned by the pair Ridwan Kamil and Uu Ruzhanul Ulum in the West Java Pilkada include the strength and network of political party coalitions, social capital that covers Ridwan Kamil's urban base, Ridwan Kamil's closeness to the news media, and the character of Uu Ruzhanul Ulum who has a mass base in the pesantren. The last is the cultural capital of Ridwan Kamil, such as his education, figures of Muslim descent and ethnicity from Sundanese origin and Uu who is a Muslim leader of kyai descent.